2022
DOI: 10.1029/2022gl099274
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence of Aerosol Radiation Modifying Photochemical Ozone Profiles in the Lower Troposphere

Abstract: Aerosol optical effects can trigger complex changes in solar shortwave radiation (SW) in the atmosphere, resulting in significant impacts on the photochemistry and vertical structure of ozone. This paper provides observational evidence of aerosol absorbing and scattering effects on modifying the SW and ozone profiles in the low troposphere. Using field vertical measurements and observation‐based model simulations, we demonstrated that absorbing aerosols decreased SW, resulting in substantial inhibition of ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There has been an increasing interest in studying the influence of atmospheric aerosols on tropospheric ozone and several research advances have been made over the last few decades (Meng et al, 1997;Pere et al, 2015;Zhu et al, 2021;Wang et al, 2022). Many studies have revealed that aerosols affect ozone by changing the photolysis frequency (Jacobson et al, 1998;Benas et al, 2013;Wang et al, 2019), some studies have quantified the impacts of absorbing aerosols on surface ozone (Li et al, 2005;Mok et al, 2016;An et al, 2021), and recent studies have compared the differences in the impacts of scattering and absorbing aerosols on ozone (Gao et al, 2022;Shi et al, 2022). Aerosols also absorb oxidative radicals, inhibit the formation of ozone in the troposphere (Jacob et al, 2000;Lou et al, 2014;Li et al, 2018), and influence ozone by altering atmospheric dynamics, that is, affect the evolution of the atmospheric boundary layer and the vertical exchange (Xing et al, 2017;Gao et al, 2020;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing interest in studying the influence of atmospheric aerosols on tropospheric ozone and several research advances have been made over the last few decades (Meng et al, 1997;Pere et al, 2015;Zhu et al, 2021;Wang et al, 2022). Many studies have revealed that aerosols affect ozone by changing the photolysis frequency (Jacobson et al, 1998;Benas et al, 2013;Wang et al, 2019), some studies have quantified the impacts of absorbing aerosols on surface ozone (Li et al, 2005;Mok et al, 2016;An et al, 2021), and recent studies have compared the differences in the impacts of scattering and absorbing aerosols on ozone (Gao et al, 2022;Shi et al, 2022). Aerosols also absorb oxidative radicals, inhibit the formation of ozone in the troposphere (Jacob et al, 2000;Lou et al, 2014;Li et al, 2018), and influence ozone by altering atmospheric dynamics, that is, affect the evolution of the atmospheric boundary layer and the vertical exchange (Xing et al, 2017;Gao et al, 2020;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to investigate the influence of aerosol optical properties on ozone using observational data (Gharibzadehet al, 2021;Shao et al, 2022). A recent study compared the influence of scattering and absorbing aerosols on ozone (Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%